Characterization and Risk Assessment of Airborne Polycyclic Aromatic Hydrocarbons From Open Burning of Municipal Solid Waste - Cheng, Ke; Li, Jing-Yu; Wang, Yan; Ji, Wan-Wan; Cao, Yi (Frontiers in Environmental Science, 2022)
In order to reveal the pollution characteristics and risk level of polycyclic aromatic hydrocarbons (PAHs) exposed to air from open burning in China, PM2.5 samples were collected from the open burning of different types of municipal solid waste (MSW). The component of MSW differed from plastics, paper, wood and bamboo, and mixed garbage. A flue gas dilution sampling system was employed to simulate open burning testing on MSW samples from different functional urban areas. Emission characteristics and health risk assessments of PAHs in PM2.5 were analyzed. The results showed that the 16 PAHs were detected ranged from 16.0 to 10,386.9 ngm−3. The total PAH concentration of wood and bamboo wastes was the highest (24,512.1 ngm−3), while that in plastics was the lowest (4,084.7 ngm−3). Speciation composition of PAHs in PM2.5 with high-molecular-weight PAHs was dominant compared to low-molecular-weight PAHs. Health risk assessment showed that the proportion of samples with the lifelong lung carcinogenic risk value greater than 10–6 was 68.7% of the totals, most of the PAHs in PM2.5 had a certain risk of cancer. The speciation of Bap posed the greatest health risks to adults and children. The carcinogenic sequence of four components of wastes was as follows: wood and bamboo > mixed garbage > paper > plastics and the risk for adults was about 2.26 times higher than for children. Totally, the PAHs speciation of BaP, DBahA, BbF, IcdP, BaA, BkF, and Chr in PM2.5 from the open burning of MSW can bring high carcinogenic risk to human health by respiratory exposure, and the risk value of adults is higher than that of children. The findings show the different conclusion with the results of related researches on the environmental effect of waste incineration power plants or incinerators. Therein, it can provide supplementary data to evaluate the impact of open burning of MSW on ambient air quality.